Demystifying Sraffa's theory of value in the light of Arrow and Debreu - Nadeem Naqvi (Philipps-University Marburg, Faculty of Business Administration and Economics, 2011)
This paper compares the models of Arrow and Debreu [1954] and Sraffa [1960], and concludes that (1) the models are informationally distinct conceptions of a capitalist economy, (2) they support radically distinct - though complete and entirely correct - theories of value, (3) the prices in the two theories are different both in terms of definitions and values, (4) in Sraffa's model it is impossible to define constant returns to scale, while in Arrow-Debreu this property is admissible, and (5) in Arrow-Debreu the interpersonal income distribution is determined whereas in Sraffa's model the distribution of income between workers and capitalists is undetermined.
Keywords: 330; constant returns to scale; theory of value; relations of production; counterfactual information; prices; exchange values; income distribution; general equilibrium; capital; marginal product; Werttheorie; Allgemeines Gleichgewicht; Theorie